Training, Retraining and Internships of Drivers (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article scientifically analyzes the current issues of training, retraining and internships for drivers. The theoretical and practical knowledge, professional competencies of drivers and the importance of advanced training in ensuring road safety are comprehensively studied. In addition, the shortcomings of the existing education system, the effectiveness of retraining and internship processes are analyzed, and specific proposals and recommendations for their improvement are given. The need to use modern innovative educational technologies to improve the professional competencies of drivers, using international best practices, is emphasized. The article serves as an important source for institutions involved in the education system and professional training in road safety, government agencies, researchers and industry experts.